Effects of administration of multivitamins and enzymes for broilers either singly or in combination on body weight and haematobiochemical parameters (Journal of the Bangladesh Agricultural University, 2010)
The experiment was conducted on “Lohman Meat” broiler chicks to evaluate the effect of exogenous multivitamin and enzyme supplementation on body weight gain, haematological parameters (TEC, Hb content, PCV and ESR) and serum transaminases (AST and ALT). A total of 20, twenty days old broilers were randomly divided into four equal groups (5×4). Group A was considered as control, fed only with commercial ration, group B was treated at a dose rate of 0.5 ml multivitamins per 1 litre of drinking water, group C was treated at a dose rate of 1 ml enzyme per litre of drinking water and group D was treated with multivitamin @ 0.5 ml/L and Enzyme @ 1ml/ L in water from 1 to 21 days of experiment. It was observed that multivitamin and enzyme supplementation significantly (p